Technique to open an ampoule with an “Ampoule Opener” tool - Rahayu, Pujen Tri; Asmiati, Dewi; Santosa, Agus (Universitas Muhammadiyah Purwokerto, 2020)
Background: The incidence of scratched by ampoule fragments while preparing medicine could harm the nurse. It needs specific tools and techniques that are effective to minimize scratches when opening an ampoule.Technique: We compared a manual ampoule opening technique and another using a unique tool, the